Influence of Copper Pretreatment on the Phase and Pore Formations in the Solid Phase Reactions of Copper with Tin - Morozovych, V.V.; Honda, A.R.; Lyashenko, Yu.O.; Korol, Ya.D.; Liashenko, O.Yu.; Cserhát, С.; Gusak, A.M. (Металлофизика и новейшие технологии, 2018)
The solid-phase reactions of copper with tin are considered, and the porosity of the reaction products depending on the pretreatment of the copper substrate is investigated. Copper substrates for the reaction are prepared by electrodeposition of copper layers with thickness of up to 100 microns on the rolled copper plates. The defects of substrates are determined by the different modes of electrodeposition—stationary, reversible, and stochastic ones. As shown, the thicknesses of the intermediate phases, their ratio, the number and spatial distribution of pores in the reaction products significantly depend on the mode of electrodeposition. The statistical dependences of the pore distribution along and across the interface as well as the characteristics of the roughness of the interface are revealed. Рассматриваются твёрдофазные реакции меди с оловом, и исследуется пористость продуктов реакции в зависимости от предварительной обработки медной подложки. Медные подложки для реакции готовятся путём электроосаждения слоёв меди толщиной до 100 мкм на прокатанные медные пластинки. Дефектность подложек определяется различными режимами электроосаждения: стационарным, реверсивным и стохастическим. Показано, что толщины промежуточных фаз, их соотношение, количество и пространственное распределение пор в продуктах реакции существенно зависят от режима электроосаждения. Установлены статистические зависимости распределения пор вдоль и поперёк интерфейса, а также характеристики его шероховатости. Розглядаються твердофазні реакції міді з циною, та досліджується поруватість продуктів реакції в залежності від попереднього оброблення мідного підложжя. Мідні підложжя для реакції готуються шляхом електроосадження прошарків міді товщиною до 100 мкм на прокатані мідні платівки. Дефектність підложжя визначається різними режимами електроосадження: стаціонарним, реверсним і стохастичним. Показано, що товщини проміжних фаз, їх відношення, кількість і просторовий розподіл пор у продуктах реакції істотно залежать від режиму електроосадження. Виявлено статистичні залежності розподілу пор вздовж і поперек інтерфейсу, а також характеристики його шерсткости.